Compliance with patient-reported outcome assessment in glioma patients: predictors for drop out. Issue 2 (31st October 2017) - Renovanz, Mirjam; Hechtner, Marlene; Kohlmann, Karoline; Janko, Mareile; Nadji-Ohl, Minou; Singer, Susanne; Ringel, Florian; Coburger, Jan; Hickmann, Anne-Katrin
Abstract: Background: Patient-reported outcomes are of high importance in clinical neuro-oncology. However, assessment is still suboptimal. We aimed at exploring factors associated with the probability for a) drop out of study and b) death during follow-up. Methods: Patients were assessed twice during follow-up visits scheduled within 3 to 5 months of each other by using 3 validated patient-reported outcome measures (t1: first assessment, t2: second assessment). As "death" was seen as a competing risk for drop out, univariate competing risk Cox regression models were applied to explore factors associated with dropping out (age, gender, WHO grade, living situation, recurrent surgery, Karnofsky Performance Status, time since diagnosis, and patient-reported outcomes assessed by Distress Thermometer, EORTC-QLQ-C30, EORTC-QLQ-BN20, and SCNS-SF-34G). Results: Two hundred forty-six patients were eligible, 173 (70%) participated. Patients declining participation were diagnosed with glioblastomas more often than with other gliomas (56% vs 39%). At t2, 32 (18%) patients dropped out, n = 14 death-related, n = 18 for other reasons. Motor dysfunction (EORTC-QLQ-BN20) was associated with higher risk for non-death-related drop out (HR: 1.02; 95% CI, 1.00–1.03; P = .03). Death-related drop out was associated with age (HR: 1.09; 95% CI, 1.03–1.14; P = .002), Karnofsky Performance Status (HR: 0.92; 95% CI, 0.88–0.96; P < .001), lower physical functioning (EORTC-QLQ-C30; HR: 0.98; 95% CI, 0.96–1.00; P = .04) and lower motor functioning (EORTC-QLQ-BN20; HR: 1.020; 95% CI, 1.00–1.04; P = .02). Conclusion: Patients with motor dysfunction and poorer clinical condition seem to be more likely to drop out of studies applying patient-reported outcome measures. This should be taken into account when planning studies assessing glioma patients and for interpretation of results of patient-reported outcome assessments in clinical routine.